Gen Z in Higher Education: Examining Leadership, Self-Efficacy, Commitment, and Performance - Gunawan, Indra; Astuti, Rini Juni (JURNAL AL-TANZIM, 2025)
This study examines the influence of transformational leadership and self-efficacy on employee performance, with organizational commitment as a mediating variable. Based on social exchange theory and Bandura's self-efficacy theory, this study aims to understand how leadership style and individual beliefs in one's own abilities can shape work outcomes in a higher education environment. A quantitative approach was employed, using a survey method with 262 Generation Z employees at a university in Yogyakarta, selected using a purposive sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) with the aid of AMOS software. The results indicate that transformational leadership and self-efficacy have a direct positive effect on employee performance, and organizational commitment has been statistically proven to play a significant mediating role in strengthening this relationship. Employees with high organizational commitment translate inspirational leadership and self-confidence into higher productivity and work effectiveness. These findings emphasize the importance of creating a supportive work environment to encourage optimal commitment and performance from Generation Z employees in higher education institutions. This research implies that developing transformational leadership, increasing self-efficacy, and strengthening organizational commitment can boost the performance of Generation Z employees in higher education.